Policy Analysis of Leadership in the Implementation of Green Campus: A Case Study at State Islamic University (UIN) Sultan Syarif Kasim Riau - Khalidah Aini (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper aims to identify and analyze the weaknesses of policies in implementing the Green Campus concept at Sultan Syarif Kasim State Islamic University (UIN) Riau. Although formal commitments have been made, implementation in the field is still far from optimal. The problem analysis reveals weaknesses in strategic vision and policies, the absence of a binding legal framework, fragmented responsibilities, and irrelevant incentive and evaluation systems. Furthermore, initiatives are not prioritized, and participation by all stakeholders is not supported by strong policies. The methodology used in this article is qualitative, with a descriptive analysis approach and case studies. Primary data were obtained through in-depth interviews with university leaders, staff, lecturers, and students involved in the desired program. Secondary data were collected from official university documents, annual reports, and related publications. Data analysis was conducted using William N. Dunn's public policy evaluation theory, specifically through multi-criteria evaluation to compare policy recommendations. Based on this analysis, recommendations are proposed to address existing weaknesses, namely the issuance of a comprehensive Rector's Decree on the Vision and Governance of a Green Campus, including the establishment of special units, permit determination, incentive systems, and participation mechanisms. This policy was deemed superior because it had the highest total in the multi-criteria evaluation, offering a holistic solution to drive transformation towards a sustainable campus.